Large Eustachian valve: An incidental finding yet perplexing - Anju Sarupria; V Bhuvana; Manju Mani; A Sampath Kumar (Annals of Cardiac Anaesthesia, 2014)
Eustachian valve (EV), a remnant of the right valve of sinus venosus in the right atrium can be puzzling. Often it is confused with Chiari network or atrial adhesions and is reported with unusual complications. We report a case of large EV impeding cannulation of inferior vena cava (IVC) during aortic valve replacement. Transesophageal echocardiography diagnosed the presence of large EV and warned of the difficulty with IVC cannulation and helped preparedness for an alternative plan during surgery.